2011
DOI: 10.1007/978-3-642-23160-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Moving towards Adaptive Search in Digital Libraries

Abstract: Abstract. Search applications have become very popular over the last two decades, one of the main drivers being the advent of the Web. Nevertheless, searching on the Web is very different to searching on smaller, often more structured collections such as digital libraries, local Web sites, and intranets. One way of helping the searcher locating the right information for a specific information need in such a collection is by providing well-structured domain knowledge to assist query modification and navigation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…We conclude that the suggestions derived from either log‐based or document‐based approaches are complementary (in those cases where they are judged relevant by the users). This is in line with findings from similar experiments conducted on digital libraries (Kruschwitz et al., ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We conclude that the suggestions derived from either log‐based or document‐based approaches are complementary (in those cases where they are judged relevant by the users). This is in line with findings from similar experiments conducted on digital libraries (Kruschwitz et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…Looking at query suggestion methods that work effectively outside the general web domain is now becoming more popular (e.g., Al Hasan, Parikh, Singh, & Sundaresan, ). Our earlier studies with individual methods for extracting query suggestions have shown promising results (e.g., Albakour, Kruschwitz ; Dignum et al., ; Kruschwitz et al., ). In this study, we investigate a more comprehensive list of different methods in a more systematic way.…”
Section: Related Workmentioning
confidence: 99%
“…It is of course perfectly reasonable to extend this and insert links that might not originally have been there or to combine this work with alternative ideas of adaptation such as adaptive search, e.g. [22,3].…”
Section: Discussionmentioning
confidence: 99%
“…For the specific experiments, we use the log files collected on an existing site search engine over a period of three years 1 to bootstrap such a model, i.e., our group profile. The idea is that query logs, the structure of logs discussed here, are segmented into sessions and then turned into a graph structure (Kruschwitz et al 2011). We then apply this profile in the summarisation process.…”
Section: Log-based Profilesmentioning
confidence: 99%